Inverse Stage Migration in Radical Prostatectomy—A Sustaining Phenomenon - Hoeh, Benedikt; Preisser, Felix; Mandel, Philipp; Wenzel, Mike; Humke, Clara; Welte, Maria-Noemi; Müller, Matthias; Köllermann, Jens; Wild, Peter; Kluth, Luis A.; Roos, Frederik C.; Chun, Felix K. H.; et al. (Frontiers in Surgery, 2021)
Objective: To investigate temporal trends in prostate cancer (PCa) radical prostatectomy (RP) candidates. Materials and Methods: Patients who underwent RP for PCa between January 2014 and December 2019 were identified form our institutional database. Trend analysis and logistic regression models assessed RP trends after stratification PCa patients according to D’Amico classification and Gleason score. Patients with neoadjuvant androgen deprivation or radiotherapy prior to RP were excluded from the analysis. Results: Overall, 528 PCa patients that underwent RP were identified. Temporal trend analysis revealed a significant decrease in low-risk PCa patients from 17% to 9% (EAPC: -14.6%, p<0.05) and GS6 PCa patients from 30% to 14% (EAPC: -17.6%, p<0.01). This remained significant even after multivariable adjustment (low-risk PCa: [OR]: 0.85, p<0.05 and GS6 PCa: [OR]: 0.79, p<0.001). Furthermore, a trend towards a higher proportion of intermediate-risk PCa undergoing RP was recorded. Conclusion: Our results confirm that inverse stage migration represents an ongoing phenomenon in a contemporary RP cohort in an European tertiary care prostate cancer center. Our results demonstrate a significant decrease in the proportion of low-risk and GS6 PCa undergoing RP and a trend towards a higher proportion of intermediate-risk PCa patients undergoing RP. This indicates a more precise patient selection when it comes to selecting suitable candidates for definite surgical treatment with RP.